2009
DOI: 10.1038/ajg.2009.314
|View full text |Cite
|
Sign up to set email alerts
|

Eradication Therapy for Helicobacter pylori in Patients With Gastric MALT Lymphoma: A Pooled Data Analysis

Abstract: This was the first comprehensive ( approximately 1,300 patients) analysis of the therapeutic management of H. pylori in gastric lymphoma patients. Data suggest that this infection is easily managed in these patients, being cured in nearly all cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 49 publications
1
58
1
5
Order By: Relevance
“…We now know that some classes of infiltrating lymphomas arise in situations where chronic infection or autoimmunity leads to sustained antigenic stimulation as occurs in Helicobacter pylori (36,37) or Hepatitis C (38, 39) infections or in autoimmune conditions, such as Sjögren syndrome (40,41) and Hashimoto thyroiditis (42,43). The prototypic example is the mucosa-associated lymphoid tissue (MALT) lymphomas that are associated with Helicobacter pylori infection and disappear in more than 75% of cases when antibiotics cure the infection, presumably because the antigen stimulation is removed (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…We now know that some classes of infiltrating lymphomas arise in situations where chronic infection or autoimmunity leads to sustained antigenic stimulation as occurs in Helicobacter pylori (36,37) or Hepatitis C (38, 39) infections or in autoimmune conditions, such as Sjögren syndrome (40,41) and Hashimoto thyroiditis (42,43). The prototypic example is the mucosa-associated lymphoid tissue (MALT) lymphomas that are associated with Helicobacter pylori infection and disappear in more than 75% of cases when antibiotics cure the infection, presumably because the antigen stimulation is removed (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…The B-cell clone that led to MALT lymphoma has been shown for cases of H. pylori-related gastritis years before the development of lymphoma (283 (234). A recent pooled data analysis of approximately 1,300 patients with gastric MALT lymphoma showed that successive attempts at H. pylori antibiotic treatment achieved eradication of infection in 98.3% of cases and that 77.8% of the H. pylori-cured patients achieved lymphoma remission (284). Unfortunately, reinfection with the same strain of H. pylori can reactivate the growth of the lymphoma.…”
Section: Antigen-driven Lymphoproliferationmentioning
confidence: 99%
“…In most cases of MALT lymphomas the malignancy disappears when the inciting H.Pylori. infection is cured by antibiotics (27)(28)(29)(30). By analogy, in the transplanted kidney there is the potential for continuous exposure to bacterial antigens by a urinary reflux mechanism in the setting of induced immunosupression.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, these findings may relate to the pathogenesis of the clonal proliferation of B-cells in other diseases such as lymphomas and myelomas where the driving forces may not be as transparent because the interactions are taking place in a less confined space. Indeed, we already know that MALT lymphomas arise because of the interaction between H. Pylori and certain B-cells in a situation not too dissimilar from that of human transplantation in terms of anatomical confinement and mechanisms that allow for enrichment of the bacterial pathogen (27)(28)(29)(30). While many more clones from infiltrating B-cells will have to be studied to generalize these findings, our results from the serum already suggest that antibody reactivity with LPS in transplant patients may be a very common phenomena.…”
Section: Discussionmentioning
confidence: 99%